Recent Advances in Surgical Orthodontics: A Narrative Review - Dhuppad, Saloni; Handa, Amit; Jadhav, Shraddha Manojkumar; Fareedoddin, Saba Anjum Siddiqui; Mane, Dipali Raghunath; Shrivastava, Himanshu; Reader, Aditi Sarda (Journal of Neonatal Surgery, 2025)
Surgical orthodontics has witnessed significant advancements over the last decade, with innovations spanning diagnostic imaging, virtual surgical planning (VSP), additive manufacturing, patient-specific implants (PSIs), navigation and augmented reality (AR), the surgery-first approach (SFA), aligner integration, airway-centered planning, and perioperative management strategies such as enhanced recovery after surgery (ERAS) and tranexamic acid (TXA). These developments collectively improve surgical accuracy, efficiency, stability, and patient-centered outcomes. This review synthesizes the current literature on seven key advances in surgical orthodontics, highlighting their clinical applications, limitations, and future research priorities.